2021
DOI: 10.1371/journal.pone.0256643
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and quality of life during COVID-19 pandemic

Abstract: COVID-19 pandemic has impacted people around the globe. Countries, including Indonesia, implemented large-scale social restrictions. Since marriage is found to be beneficial to people’s quality of life (QoL), the study aimed to examine the QoL of married people in Indonesia during a large-scale social restriction of the COVID-19 pandemic. An online cross-sectional survey using Qualtrics was conducted in June 2020. Respondents’ sociodemographic data, spouse data (as reported by the respondents), and pandemic-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 37 publications
3
27
3
Order By: Relevance
“…Regarding intrahepatic fat content measured by nuclear magnetic resonance (IFC-NMR), it should be mentioned that results with significant differences were obtained with previous adjustments to the data in the current study (p = 0.001; data not shown). However, when socioeconomic and marital status were introduced in the current adjustment, the significance disappeared, which allows us to understand that these were two important factors during lockdown [46,47] that nullified the differences in liver fat according to PA groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding intrahepatic fat content measured by nuclear magnetic resonance (IFC-NMR), it should be mentioned that results with significant differences were obtained with previous adjustments to the data in the current study (p = 0.001; data not shown). However, when socioeconomic and marital status were introduced in the current adjustment, the significance disappeared, which allows us to understand that these were two important factors during lockdown [46,47] that nullified the differences in liver fat according to PA groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a global village world, education plays a major role especially when it comes to the sharing economy, as the majority of the transactions are online, and there is a need for one to have a basic level of education in operation. This education is believed not only to help the members within a community to transact but also to live a better life, evidenced by some studies that attest to the fact that those with a good level of education tend to have a better life ( Campos et al, 2014 ; Purba et al, 2021 ). The findings of this study have also revealed that the majority of the members were relatively mature in age, falling above 30 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In continuation, we have found that there is a positive correlation or association between the availability of disposable funds and education’s members agreed that VSLAs led to an increase in disposable funds which in turn is being used to pay for their education expenses, something which is paramount for human development and individual QOL and wellbeing as per our discussion. Another explanation for this fact is that there is a high probability that most of the educated members of VSLAs had a better QOL and wellbeing due to their exposure or knowledge of public health as well as various means of income-generating opportunities ( Campos et al, 2014 ; Purba et al, 2021 ). Our findings are also consistent with a study on education and quality of life which found that higher tertiary educational achievement leads to occupations likely to provide the opportunity for continued refinement of the cognitive and interpersonal skills which is also believed to promote community wellbeing ( Edgerton et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Married people, especially women, those with low levels of education, and those currently out of work or with a below-average financial condition reported lower QoL during the pandemic [ 28 ]. Low-income and single patients were three-to-four times more likely to report a reduction in usual activities five months after diagnosis, in line with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%